2015
DOI: 10.1128/aem.04252-14
|View full text |Cite
|
Sign up to set email alerts
|

Houseflies (Musca domestica) as Vectors for Extended-Spectrum β-Lactamase-Producing Escherichia coli on Spanish Broiler Farms

Abstract: bFlies may act as potential vectors for the spread of resistant bacteria to different environments. This study was intended to evaluate the presence of Escherichia coli strains resistant to cephalosporins in flies captured in the areas surrounding five broiler farms. Phenotypic and molecular characterization of the resistant population was performed by different methods: MIC determination, pulsed-field gel electrophoresis (PFGE), multilocus sequence typing (MLST), and phylotyping. The presence of extended-spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(43 citation statements)
references
References 48 publications
0
40
0
3
Order By: Relevance
“…Previous studies have discussed the role of flies as vectors of antimicrobial resistance bacteria (Blaak et al, 2014;Davari et al, 2010;Literak et al, 2009;Liu et al, 2013;Macovei and Zurek, 2006;Marshall et al, 1990;Rahuma et al, 2005;Rybaříková et al, 2010;Schaumburg et al, 2016;Solà-Ginés et al, 2015;Usui et al, 2015Usui et al, , 2013Von Salviati et al, 2015;Wang, 2013;Wang et al, 2017;Zurek and Ghosh, 2014). In Brazil, Almeida et al (2014) isolated E. coli, Salmonella spp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have discussed the role of flies as vectors of antimicrobial resistance bacteria (Blaak et al, 2014;Davari et al, 2010;Literak et al, 2009;Liu et al, 2013;Macovei and Zurek, 2006;Marshall et al, 1990;Rahuma et al, 2005;Rybaříková et al, 2010;Schaumburg et al, 2016;Solà-Ginés et al, 2015;Usui et al, 2015Usui et al, , 2013Von Salviati et al, 2015;Wang, 2013;Wang et al, 2017;Zurek and Ghosh, 2014). In Brazil, Almeida et al (2014) isolated E. coli, Salmonella spp.…”
Section: Discussionmentioning
confidence: 99%
“…After detecting E. coli clones from flies and calf feces with the same antimicrobial resistance profile, Usui et al (2015Usui et al ( , 2013 suggested that flies can disseminate antimicrobial resistance genes not only within farm but also between farms. Similarly, Solà-Ginés et al (2015) found the same Extended-spectrum β-lactamase (ESBL)-producing E. coli clone isolated from flies within two broiler farms and suggested it may have happened because flies can travel long distances.…”
Section: Introductionmentioning
confidence: 95%
“…Penelitian skala laboratorium di Iran membuktikan bahwa lalat Musca domestica memiliki peran penting dalam menyebarluaskan beberapa bakteri yang resisten terhadap antibotik. 26,63,64 Risiko menjadi lebih besar saat bakteri yang berada dalam kotoran dan dengan mudah tertelan dan masuk dalam tubuh lalat, lalat dapat meningkatkan transmisi resistensi antimikroba pada bakteri yang berkembang biak dalam saluran pencernaan, bagian mulut dan muntahan lalat. 8…”
Section: Potensi Epidemi Dan Resistensi Antimikrobaunclassified
“…Previous studies have shown food and the environment to contain ARG found in pathogenic bacteria (12, 23, 24). Environmental reservoirs of ARG-containing pathogens include lakes and rivers (18), wastewater treatment plants (25, 26), houseflies (27), livestock (12, 28, 29), soil and manure (29, 30), retail meat products (12, 3133), companion animals (5, 6, 8, 28, 34), alfalfa sprouts (35), retail spinach (15), and other vegetables (36). The findings from these studies indicate that human health may be impacted by uptake of pathogens from the environment, many of which harbor ARG on mobile genetic elements.…”
Section: Introductionmentioning
confidence: 99%